(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The industrial trajectory of Tamil Nadu exemplifies a structured and successful economic transition. It evolved from an initial foundation in light industries, notably textiles in the Coimbatore region, leveraging agro-based resources and early power availability. A pivotal shift occurred mid-20th century with the strategic establishment of public sector heavy industries like BHEL and NLC, embedding core engineering and manufacturing capabilities. Post-1990s economic liberalization accelerated this transformation, propelling the state to become a global automotive hub and a leading IT services exporter. Consequently, Tamil Nadu’s industrial landscape has matured into a unique, diversified synthesis of traditional light sectors, capital-intensive heavy industries, and modern knowledge-based services, solidifying its status as an economic powerhouse in India.